Distal locking of femoral nails: a prospective comparative study of two different fluoroscopy assisted techniques - Patra, Saroj Kumar; Patro, Bishnu Prasad; Samal, Sidharth; Sahu, Mahesh Chandra; Mohanty, Biswa Bhusana (International Surgery Journal, 2016)
Background: The purpose of this study is to compare the radiation exposure and time required for distal femoral locking by two different fluoroscopy dependent free hand techniques. Methods: Two different free hands fluoroscopic assisted distal locking of femur was adopted. First one, traditional method of locking femur in which free hand drilling of femur done with lateral view of femur. Second one is one where femur was drilled with anterior-posterior view of femur in image intensifier. In each method 150 femurs was operated. All the surgeries are performed by same surgeons. Total time duration for distal locking and radiation exposures in terms of fluoroscopy shots in each procedure was compared. Results: The time duration of distal locking with this novel method (second) was only 4 mins (average) and number of fluoroscopy shots are 8 (average) which is significantly less than routine freehand technique (first) i.e. 14 min (average) and 18 (average) fluoroscopy shots. Conclusions: Our novel method is significantly less time consuming and minimal radiation exposure compared to traditional free hand technique.